Needs Assessment for the Global-Mindedness of Vocational Certificate Students under the Office of the Vocational Education Commission - Ancharee Chainut; Peerawut Suwanjan; Phadungchai Pupat; Paitoon Pimdee (My University, 2019)
Abstract The objectives of the research are as follows: 1) to study the global-mindedness of vocational certificate students; 2) to compare the global-mindedness of these students by grade level, with a sample group of 361 vocational certificate students studying at the vocational certificate level in the 2016 academic year, obtained by stratified random sampling, and 3) to rank the needs for the global-mindedness of these students. The instruments used in the data collection consisted of a questionnaire on the global-mindedness expectation and authenticity of vocational certificate students, which contained 40 questions, covering four aspects, evaluated for content validity by qualified experts. The statistics used in the data analysis were mean, standard deviation, one-way analysis of variance, and the Modified Priority Needs Index (PNI). The research findings are as follows: 1) the level of global-mindedness of the vocational certificate students is high; 2) there were no differences in the global-mindedness of vocational certificate students studying at different grade levels; 3) the needs, ranked in descending order, consisted of acceptance of cultural diversity, attention to global issues, interconnectedness and peace, and world citizenship.
Keywords: Certificate; Stratified Sampling; Sample (material); Education and Critical Thinking Development